Cyber-Nasionalisme Dan Diplomasi Publik Digital: Studi Tentang Analisis Narasi Influencer Indonesia Terhadap Isu Palestina-Israel Di Platform X - Kezia Agustin Kristiania; Sih Natalia Sukmi; Triesanto Romulo Simanjuntak (Spektrum, 2026)
This research is motivated by the shift in public diplomacy articulation from state actors to the digital realm through cyber-nationalism, where a literature gap remains regarding the structural mechanisms of influencers in constructing such discourse. Therefore, this study aims to analyze how Indonesian influencers construct cyber-nationalism discourse regarding the Palestine-Israel issue on platform X, and to evaluate the contribution of these narratives to the formation of Indonesia's soft power image. Utilizing a descriptive qualitative approach with Norman Fairclough's Critical Discourse Analysis (CDA) method, this research examines textual data from the @erlanishere account from October 2023 to December 2024. The results indicate that pro-Palestinian narratives are structurally constructed through linguistic strategies that delegitimize colonization and validate historical-legal truths. At the discursive and sociocultural levels, this discourse activates the nation's constitutionally based collective memory, transforming the audience into discourse co-producers who actively mobilize solidarity. These findings confirm that digital campaigns like #JulidFiSabilillah serve as grassroots public diplomacy instruments that significantly strengthen Indonesia's moral authority and soft power in the global political structure without relying exclusively on formal diplomatic channels.